Proses Penanganan Clearance Out Karantina pada Sistem Single Submission Kapal MT. Jupiter Star - Yelvianus Wau; Yursal Yursal; Yusnidah Yusnidah (Jurnal Transformasi Bisnis Digital, 2025)
This paper discusses the quarantine clearance out handling process through the SSM Single Submission System for the issuance of the Port Health Quarantine Certificate PHQC on the MT Jupiter Star ship managed by PT Semesta Sejahtera Lestari, Lampung Branch. Quarantine clearance out is an important stage in ensuring that ships departing from the port meet all health requirements and are free from the threat of diseases that can be transmitted to other areas. This process begins with the submission of an application by the ship's agent through the SSM System, which is designed to facilitate interaction between various related agencies, including the KKP Port Health Office, Customs, Immigration, and Ksop. After the application is submitted, quarantine officers will conduct a health inspection of the ship, including an examination of the crew and other health documentation. The results of this inspection are then recorded in the system and, if all requirements are met, a PHQC will be issued. This paper also identifies the challenges faced in the process, such as data integration between agencies that is sometimes less than optimal, and the importance of improving coordination between related parties to ensure a smooth clearance out process. Ultimately, the implementation of the SSM system is expected to increase efficiency and transparency in the process of issuing port health certificates, which in turn supports the smooth running of international shipping and trade activities. In writing this paper, the author used field research and library research methods.